Risk factor analysis of bronchospasm after tracheobronchial foreign body removal: Cases report and literature review (STROBE) - Cui, Yu (Medicine (Baltimore), 2020)
This retrospective study aimed to investigate bronchospasm after tracheobronchial foreign body removal. Bronchoscopy is the main clinical treatment for removing airway foreign bodies, but postoperative airway spasm is very common. In our study, we perform a risk factor analysis of bronchospasm after tracheobronchial foreign body removal. The sample was composed of 261 children with airway foreign bodies who had undergone clinical bronchoscopy for foreign body removal under general anesthesia were enrolled from the department of otolaryngology, the First Hospital of Jilin University from 2014 to 2019, of which 78 in the left bronchus, 107 in the right bronchus, 51 in the main bronchus, and 25 in the subglottis. All patients were confirmed by radiographic examination or pulmonary auscultation. All their medical records and clinical data were retrospectively analyzed; single factor and multiple factor analyses of bronchospasm were performed. The logistic regression analysis showed that age, foreign body retention time and operation time were independent risk factors for postoperative airway spasm. A history of pneumonia was not an independent risk factor for postoperative airway spasm. We should pay more attention in the preoperative period according to the specific situation of child; the right means of anesthesia and appropriate hormonal drugs should be chosen to prevent the occurrence of postoperative airway spasm.